METAPHORICAL REPRESENTATION OF THE CONCEPT CONFLICT IN AMERICAN AND BRITISH POLITICAL DISCOURSE (BASED ON IMAGE METAPHORS) - Ковалюк, Мирослава Володимирівна; Федич, Ганна Дмитрівна (Рута, 2023)
The article is devoted to the metaphorical representation of the concept CONFLICT in the English-language political discourse, namely American and British. The figurative content of the concept CONFLICT is realized through a metaphorical image, which clarifies the essence of the CONFLICT more profoundly by means of its figurative assimilation to other entities in the context of modern English-language political discourse. Metaphorical images are revealed on the basis of the cognitive-discursive interpretation of the discursive contexts of the metaphorical nomination with the involvement of the tools of the cognitive metaphor theory. The article defines the notion of conceptual metaphor in cognitive linguistics, explains the definition of image metaphor and establishes the specifics of the metaphorical actualization of the concept CONFLICT in modern political discourse by representatives of American and British culture. The analysis of the speeches of English-speaking political leaders between 2000-2020 showed that CONFLICT is represented by the following image metaphors: CONFLICT is ideological STRUGGLE, CONFLICT is LAST RESORT, CONFLICT is TEST, CONFLICT is CONTEST, CONFLICT is METAPHOR, CONFLICT is CLASH, CONFLICT is MISTAKE, CONFLICT is SPORT, CONFLICT is EXPERIENCE, CONFLICT is CALLING, CONFLICT is BIG MATTER, CONFLICT is DIFFICULT PROPOSITION, CONFLICT is BIG CONTROVERSIAL ISSUE, CONFLICT is AN INTERESTING WAY TO DESCRIBE THE WORLD WE LIVE IN, CONFLICT is COMPLEX MISSION, CONFLICT is IMAGE, CONFLICT is ENFORCING DOCTRINE, CONFLICT is TRAGEDY, CONFLICT is RESPONSIBILITY, CONFLICT is NOT OPTIMISTIC THOUGHT, CONFLICT is SUBJECT, CONFLICT is DAMAGE, CONFLICT is DISASTER, CONFLICT is BLOODY AND BRUTAL BUSINESS, CONFLICT is MEASUREMENT, CONFLICT is BOND, CONFLICT is PARALLEL, CONFLICT is VICTORY, CONFLICT is primarily intelligence and law enforcement operation,CONFLICT is SCAR, CONFLICT is DISEASE, CONFLICT is LOSER, CONFLICT is REALM OF UNCERTAINTY, CONFLICT is CREATION, CONFLICT is PLEDGE, CONFLICT is RELICS, CONFLICT is EXPRESSION OF HUMAN FOLLY, CONFLICT is CHAPTER OF HISTORY, CONFLICT is DISTANT MEMORY, CONFLICT is REMORSELESS SCAVENGER, CONFLICT is SURPASSING IRONY, CONFLICT is (not) WORD, CONFLICT is (not) CRUSADE, CONFLICT is UNJUSTIFIED PROVOCATION, CONFLICT is WORST POSSIBLE SOLUTION, CONFLICT is TASK, CONFLICT is MORAL, CONFLICT is OPTION, CONFLICT is ANSWER, CONFLICT is FESTING WOUND. Image metaphors depict the CONFLICT in the most unusual comparisons and similes, which are actualized both by political representatives of American and British society
Keywords: conceptual metaphor, political discourse, image metaphor, American linguaculture, British linguaculture.